Exploring the Use of Blooket in Arabic Vocabulary Instruction: Evidence from a Secondary School in Indonesia - Alfa Alchairiah; Miatin Rachmawati (ATHLA : Journal of Arabic Teaching, Linguistic and Literature, 2026)
This study was motivated by the suboptimal learning of Arabic vocabulary, which is still dominated by traditional methods, resulting in low student motivation and participation. Therefore, technology-based learning media that can create a more engaging and interactive learning environment are needed. This study used a qualitative The study aims to explore the use of Blooket in Arabic vocabulary learning and to examine the perceived benefits and challenges. Data were collected through observation, interviews, and documentation. The data obtained were then analyzed using the Miles and Huberman model, which includes the stages of data reduction, data presentation, and the drawing and verification of conclusions. This approach was used to systematically identify, organize, and interpret research findings in accordance with the study’s focus. The results indicate that the use of the Blooket app in Arabic vocabulary instruction enhances student motivation, active participation, and enthusiasm during the learning process. The integration of game elements and interactive quizzes helps students understand and retain vocabulary more effectively, thereby supporting improved retention of the material. The research findings also indicate that the learning environment becomes more engaging and encourages more intensive student involvement. However, the implementation of Blooket still faces several challenges, such as limited internet connectivity, the availability of supporting devices, and the need for greater preparation time on the part of teachers. Future research should investigate the long-term effects of game-based learning platforms on Arabic vocabulary mastery across various educational settings.